1990
DOI: 10.1080/02640419008732130
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of rugby union scrummaging

Abstract: Two rugby union forward packs of differing ability levels were examined during scrummaging against an instrumented scrum machine. By systematically moving the front-row of the scrum along the scrum machine, kinetic data on each front-row forward could be obtained under all test conditions. Each forward pack was tested under the following scrummaging combinations: front-row only; front-row plus second-row; full scrum minus side-row, and full scrum. Data obtained from each scrum included the three orthogonal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
105
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(116 citation statements)
references
References 1 publication
8
105
3
Order By: Relevance
“…Effective scrummaging requires coordinated pushing by the eight players (Trewartha, Preatoni, England, & Stokes, 2014), which produces forces greater than the sum of each forward's individual scrummaging force (Quarrie & Wilson, 2000). Unsurprisingly, scrum engagement forces are positively related to the total body mass of the opposing pack (Du Toit, Olivier, & Buys, 2005;Milburn, 1990). Rugby players' size has increased markedly over the last 25 years (Sedeaud et al, 2012) and therefore, engagement forces have doubled since 1990 (8000 N vs. 16500 N) (Milburn, 1990;Preatoni, Stokes, England, & Trewartha, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Effective scrummaging requires coordinated pushing by the eight players (Trewartha, Preatoni, England, & Stokes, 2014), which produces forces greater than the sum of each forward's individual scrummaging force (Quarrie & Wilson, 2000). Unsurprisingly, scrum engagement forces are positively related to the total body mass of the opposing pack (Du Toit, Olivier, & Buys, 2005;Milburn, 1990). Rugby players' size has increased markedly over the last 25 years (Sedeaud et al, 2012) and therefore, engagement forces have doubled since 1990 (8000 N vs. 16500 N) (Milburn, 1990;Preatoni, Stokes, England, & Trewartha, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…40 It has been shown that the impulsive impact force on a scrum engagement exceeds the threshold of injury to the spine. 23 This emphasises firstly the importance of specific scrum technique training, which includes correct alignment of the head, neck and trunk, and adequate back, shoulder and neck strength to maintain a safe body position during engagement. 23,36 More than 90% of scrum-related catastrophic cervical spine injuries occurred during either scrum engagement (47%) or a collapsed scrum (46%).…”
mentioning
confidence: 99%
“…23 This emphasises firstly the importance of specific scrum technique training, which includes correct alignment of the head, neck and trunk, and adequate back, shoulder and neck strength to maintain a safe body position during engagement. 23,36 More than 90% of scrum-related catastrophic cervical spine injuries occurred during either scrum engagement (47%) or a collapsed scrum (46%). 30 The remainder of injuries were caused by front-row forwards actively extending their necks and driving the opposite front-row upwards; this has been termed 'popping', 25 or more recently 'scrumming up'.…”
mentioning
confidence: 99%
See 2 more Smart Citations